The effect of culture on financial regulation policies - Foo, Jun Jie (2019)
While an individualistic society values self-reliance, risk taking, encourages autonomy, rewards personal achievements, a collectivistic society prizes conformity, interdependence and values the significance of the in-group which the individual belongs to. There has been a widespread belief that individualism promotes economic development directly by strengthening an individual’s incentive to make rational economic decisions to invest, innovate and accumulate further wealth. Given the expanding body of empirical and theoretical framework towards the belief that financial liberalization is one of the most crucial factors to economic growth, this paper attempts to fill the gap by investigating the impact of individualism on financial liberalization. This paper examines how individualism, which we believe is a critical root to financial reform, influences the level of financial liberalization. In addition, cross cultural psychologists have identified individualism-collectivism as the most significant cultural dimension. We hypothesize that the effect of individualism should exert a positive impact on the degree of financial liberalization. Using data on financial liberalization index during the years 1980 to 2005 for approximately 60 countries, our empirical evidences substantiate the strong positive relationship of individualism and financial liberalization, especially in countries possessing high scores for certain country characteristics. In addition, our results remain statistically significant after sets of robustness checks.